Comparative Lipidomic and Metabolomic Analyses Reveal the Mystery of Lacquer Oil from Toxicodendron vernicifluum for the Treatment of “Yuezi” Disease in Nujiang, China: From Anti-Inflammation and Anti-Postpartum Depression Perspective - Liu, Liya; Cai, Fei; Lu, Yitong; Xie, Yuting; Li, Hao; Long, Chunlin (Frontiers in Pharmacology, 2022)
Background: In southwest China, especially in Nujiang, lacquer oil from the drupes of Toxicodendron vernicifluum (Stokes) F. A. Barkley, includes black lacquer oil (BLO) and white lacquer oil (WLO), and is one of the most important edible oils for the local people. Through the field investigation, the locals believe that lacquer oil has benefits for parturient women and for the treatment of “Yuezi” disease. However, studies on bioactivities and the chemical compositions of lacquer oil are limited. Purpose: This study was designed to reveal the mystery of lacquer oil for the treatment of “Yuezi” disease by testing its anti-inflammatory and anti-postpartum depressant activities and related bioactive compounds. Methods: The anti-inflammatory effects of lacquer oil were examined by establishing a lipopolysaccharide (LPS)-induced RAW264.7 cell inflammation model and detecting the level of pro-inflammatory factors such as NO, IL-6 and TNF-α. The antidepressant effects of lacquer oil were studied by building a mouse model of postpartum depression (PPD), and the animal behavior changes of PPD model mice were assessed by open field test (OFT), forced swimming test (FST) and tail suspension test (TST). The lipidomic and chemical profiles of BLO and WLO were detected by lipidomic and the untargeted metabolomic research methods based on UPLC-MS/MS. Results: The results showed that BLO and WLO exerted anti-inflammatory effects by reducing the release of pro-inflammatory factors and BLO had better anti-inflammatory effects than WLO. While only BLO had anti-postpartum depressant activities, as evidenced by the significantly reduced the immobility time of the BLO-treated PPD mice in TST and FST compared to the PPD model mice. The comparative lipidomic analysis revealed that BLO contained high levels of Diacylglycerols (DAG) and Diacylglyceryl trimethylhomoserines (DGTS) but low level of ceramides (Cer), sphingomyelines (SM), phosphatidylcholines (PC) and phosphatidylethanolamines (PE) compared with WLO. Metabolomics analysis showed that there were 57 chemical markers between BLO and WLO, of which 17 potential biomarkers have been declared to possess anti-inflammatory and/or antidepressant activities. Conclusion: The findings of this study furnish scientific support for the traditional uses of lacquer oil for the treatment of “Yuezi” disease from anti-inflammation and anti-postpartum depression perspective.